Microcavities - Kavokin, Alexey, 1970- (Oxford : Oxford University Press, 2007)
This volume covers a new and rapidly developing research field in physics. Confining light in small structures called microcavities produces new devices which exploit the quantum physics of light matter interactions.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Lasers; Quantum electrodynamics; Electromagnetic interactions; Semiconductors